2017
DOI: 10.7554/elife.28132
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modulation of activity in cerebellar nuclei neurons during pavlovian eyeblink conditioning in mice

Abstract: While research on the cerebellar cortex is crystallizing our understanding of its function in learning behavior, many questions surrounding its downstream targets remain. Here, we evaluate the dynamics of cerebellar interpositus nucleus (IpN) neurons over the course of Pavlovian eyeblink conditioning. A diverse range of learning-induced neuronal responses was observed, including increases and decreases in activity during the generation of conditioned blinks. Trial-by-trial correlational analysis and optogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
167
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(176 citation statements)
references
References 92 publications
(181 reference statements)
6
167
3
Order By: Relevance
“…The inferior olive is the sole source of the climbing fibers, the activity of which dictates complex spike firing by cerebellar Purkinje cells (for review, see (20)). Climbing fiber activity is essential for motor coordination, as it contributes to both initiation and learning of movements (8, 10, 2126), and it may also be involved in sensory processing and regulating more cognitive tasks (2730). Understanding the systemic consequences of inferior olivary spiking is therefore of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The inferior olive is the sole source of the climbing fibers, the activity of which dictates complex spike firing by cerebellar Purkinje cells (for review, see (20)). Climbing fiber activity is essential for motor coordination, as it contributes to both initiation and learning of movements (8, 10, 2126), and it may also be involved in sensory processing and regulating more cognitive tasks (2730). Understanding the systemic consequences of inferior olivary spiking is therefore of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, spike coding from thalamus to motor cortex is depending on recovery from synaptic depression during a pause in high-frequency CN spiking. Such pauses are found during several behavioral paradigms (Ohmae et al 2013;Ten Brinke et al 2017). For instance, during natural running on a treadmill the CN firing rate rises above 100 Hz during the lift of the paw and decreases sharply during the 100 ms before paw movement (Sarnaik and Raman 2018).…”
Section: Discussionmentioning
confidence: 97%
“…It is well-established that the cerebellum plays a key role in motor control and coordination (Stoodley and Schmahmann, 2010). More recent studies have suggested that it can also encode expectation for sensory outcomes (Brinke et al, 2017;Sawtell, 2017;Wagner et al, 2017) as well as that its activity is necessary to maintain cortical preparatory activity in motor planning (Gao et al, 2018). Thus, given our above observations on the pre-motor decision-dependent dPCs of the cerebellum and ARTR, we hypothesize that they may represent preparatory neuroactivity for motor response, similar to what has been reported in the cortex (Churchland et al, 2012;Gao et al, 2018;Li et al, 2016).…”
Section: Preparatory Neuroactivity In Cerebellum and Artr Predict Decmentioning
confidence: 99%